Standardisation of Soil Sampling and Fertilizer Recommendation Techniques for Coconut Gardens - Nimba Frango E F (Department of Soil Sciences and Agricultural Chemistry, College of Horticulture, 1998)
An investigation was carried out during 1994-95 to standardise soil sampling technique for coconut and to work out fertilizer recommendation system considering physical/textural nature of soil as well as nutrient levels. Two standing populations of WeT palms grown under good and average management practices (situation A and B respectively) located at Mulamkunnathukavu (Thrissur district) was utilised for the study. From each plot twenty healthy palms were selected for the study. The coconut gardens were separated by a distance of about 1 km and the soil of the site was laterite (Oxisol). Composite soil samples were collected from three depths from the surface and from three radial positions from the bole of the palm. Samples were collected in May, October and January. Leaf samples were collected from the 10th frond and observations on yield and yield attributes were also recorded along with soil samples. Physico-chemical properties of soil, root activity pattern, leaf nutrient content and yield and yield attributes of both situations were compared. Correlation between physical and chemical properties of soil, correlation between soil parameters, leaf nutrient content, yield and yield attributes were also worked out. Both situations showed much variation in physico-chemical properties of soil. Coarser soil fractions were more in situation B while, in situation A finer fractions dominated. High yield situation (situation A) recorded higher values for organic carbon and available K compared with situation B. Depthwise as well as radial distance wise differences were also noticed in the nutrient content. In both